Systemic acquired resistance, NPR1, and pathogenesis-related genes in wheat and barley - Xiao-dong WANG; Wei-shuai BI; Jing GAO; Xiu-mei YU; Hai-yan WANG; Da-qun LIU (Journal of Integrative Agriculture)
In Arabidopsis, systemic acquired resistance (SAR) is established beyond the initial infection by a pathogen or is directly induced by treatment with salicylic acid (SA) or its functional analogs, 2,6-dichloroisonicotinic acid (INA) and benzothiadiazole (BTH). NPR1 protein is considered the master regulator of SAR in both SA signal sensing and transduction. In wheat (Triticum aestivum) and barley (Hordeum vulgare), both pathogen infection and BTH treatment can induce broad-spectrum resistance to various diseases, including powdery mildew, leaf rust, Fusarium head blight, etc. However, three different types of SAR-like responses including acquired resistance (AR), systemic immunity (SI), and BTH-induced resistance (BIR) seem to be achieved by activating different gene pathways. Recent research on wheat and barley NPR1 homologs in AR and SI has provided the initial clue for understanding the mechanism of SAR in these two plant species. In this review, the specific features of AR, SI, and BIR in wheat and barley were summarized and compared with that of SAR in model plants of Arabidopsis and rice. Research updates on downstream genes of SAR, including pathogenesis-related (PR) and BTH-induced genes, were highlighted.